Impact of mean arterial pressure on clinical outcomes in comatose survivors of out-of-hospital cardiac arrest: Insights from the University of Ottawa Heart Institute Regional Cardiac Arrest Registry (CAPITAL-CARe). (April 2017) - Russo, Juan J.; James, Tyler E.; Hibbert, Benjamin; Yousef, Altayyeb; Osborne, Christina; Wells, George A.; Froeschl, Michael P.V.; So, Derek Y.; Chong, Aun Yeong; Labinaz, Marino; Glover, Chris A.; Marquis, Jean-François; et al.
Abstract: Aim of the study: We sought to assess the relationship between mean arterial pressure (MAP) and clinical outcomes in comatose survivors of out-of-hospital cardiac arrest (OHCA). Methods: We identified consecutive comatose survivors of OHCA with an initial shockable rhythm treated with targeted temperature management. We examined clinical outcomes in relation to mean MAP (measured hourly) during the first 96 h of hospitalization. Co-primary outcomes were the rates of death and severe neurological dysfunction at discharge. Results: In 122 patients meeting inclusion criteria, death occurred in 29 (24%) and severe neurological dysfunction in 39 (32%). Higher mean MAPs were associated with lower odds of death (OR 0.55 per 5 mmHg increase; 95%CI 0.38–0.79; p = 0.002) and severe neurological dysfunction (OR 0.66 per 5 mmHg increase; 95%CI 0.48–0.90; p = 0.01). After adjustment for differences in patient, index event, and treatment characteristics, higher mean MAPs remained associated with lower odds of death (OR 0.60 per 5 mmHg increase; 95%CI 0.40–0.89; p = 0.01) but not severe neurological dysfunction (OR 0.73 per 5 mmHg increase; 95%CI 0.51–1.03; p = 0.07). The relationship between mean MAP and the odds of death (p-interaction = 0.03) and severe neurological dysfunction (p-interaction = 0.03) was attenuated by increased patient age. Conclusion: In comatose survivors of OHCA treated with target temperature management, a higher mean MAP during the first 96 h of admission is associated with increased survival. The association between mean MAP and clinical outcomes appears to be attenuated by increased age.